2007
DOI: 10.1002/crat.200610847
|View full text |Cite
|
Sign up to set email alerts
|

Growth and characterization of a PbI2 single crystal used for gamma ray detectors

Abstract: Lead iodide (PbI 2 ) is an important material for room temperature radiation detectors. In this paper, we have grown PbI 2 single crystal through a special craft, from which γ-ray detector has also been fabricated. X-ray diffraction analysis indicates structure of the grown crystal is 2H with hexagonal space group P3m1. Infrared transmission measurement shows transmission rate of the grown crystal sample (10×10×1mm 3 ) reaches 40% averagely in range of 400~4000cm . Ultraviolet absorbing test indicates cut-off … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 10 publications
(10 reference statements)
4
37
0
3
Order By: Relevance
“…It can be inferred from the observed and JCPDS data of table 1 that the strongest peaks are observed for d values 2.33 Å and 1.75 Å respectively correspond to the plane (0 0 3) and (0 0 4). The XRD analysis confirmed that PbI 2 films are polycrystalline, having hexagonal structure [11]. The raw X-ray data repeatedly modified by means of Gaussian fit enabled one to build up the present figure (Fig.…”
Section: Methodsmentioning
confidence: 54%
“…It can be inferred from the observed and JCPDS data of table 1 that the strongest peaks are observed for d values 2.33 Å and 1.75 Å respectively correspond to the plane (0 0 3) and (0 0 4). The XRD analysis confirmed that PbI 2 films are polycrystalline, having hexagonal structure [11]. The raw X-ray data repeatedly modified by means of Gaussian fit enabled one to build up the present figure (Fig.…”
Section: Methodsmentioning
confidence: 54%
“…Recently, polycrystalline PbI 2 thick films have attracted lots of attention for digital X‐ray flat‐panel detector (FPD) applications combined with large‐area thin‐film transistor (TFT) array substrates . Several effective methods have been employed for PbI 2 single‐crystal growth, such as traveling molten zone (TMZ) , zone melting , vertical Bridgman , Czochralski , and vapor transport . Also, it is certain that highly purified PbI 2 is needed when used for crystal growth and detection application .…”
Section: Introductionmentioning
confidence: 99%
“…The transmission rate of the two crystals reaches 50% in the range of 4000∼400 cm −1 . This value is higher than that has been reported, generally 40∼45% . Based on the solid state physics theory, the theoretical infrared transmission rate of the PbI 2 crystal can be calculated to be 58.8% .…”
Section: Resultsmentioning
confidence: 59%